Taxes and cross-border cooperation in the system of state regional policy (Economics and region, 2025)
This article explores the pivotal role of taxation and cross-border cooperation in the development of an effective state regional policy in Ukraine, focusing on their impact on sustainable regional growth and economic integration. The study provides a comprehensive analysis of the current state of Ukraine’s national legislation concerning taxation, particularly its implications for regional development, and evaluates the mechanisms facilitating cross-border interactions between Ukrainian regions and neighboring countries. It identifies critical challenges, including the uneven distribution of tax revenues across regions, which often exacerbates economic disparities, and the limited integration of cross-border initiatives into the broader framework of regional governance. These issues hinder the potential for balanced regional development and economic cohesion. A significant focus is placed on the effects of decentralization reforms on local budget formation through tax revenues. The article examines how decentralization has empowered local authorities to manage fiscal resources more autonomously, yet it also highlights the persistent challenges of ensuring equitable tax distribution and efficient resource allocation. Furthermore, the potential of cross-border cooperation is analyzed as a strategic tool for attracting foreign investments, fostering economic growth in border regions, and promoting cross-border trade. The study delves into the mechanisms of coordination between local governments, state institutions, and international partners, emphasizing the importance of collaborative frameworks in achieving regional policy objectives. Special attention is given to the alignment of Ukraine’s tax policies with European standards, particularly in the context of cross-border cooperation. This alignment is crucial for enhancing Ukraine’s integration into the European economic space and ensuring compatibility with international fiscal practices. The article proposes actionable measures to strengthen the legislative framework, including reforms to optimize tax revenue distribution, enhance fiscal transparency, and support cross-border initiatives through targeted funding and policy incentives. It also underscores the importance of interregional and international agreements in bolstering the economic potential of regions, particularly those along Ukraine’s borders.
Keywords: taxes; cross-border cooperation; regional policy; decentralization; local budgets; state governance; European integration; investments